2015
DOI: 10.1111/add.12838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warning statements in e‐cigarette advertisements: an experiment with young adults in the United States

Abstract: Background and Aims This on-line experiment examined whether the addition of ingredient- or industry-themed warning statements in television advertisements for e-cigarettes would affect young adults’ craving for and risk perceptions of e-cigarettes and combustible cigarettes, as well as intent to purchase e-cigarettes. Design Advertisements for two leading e-cigarette brands were edited to contain a warning statement about product ingredients or about the tobacco industry. Participants were assigned randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
2
49
1
Order By: Relevance
“…Additionally, smoking men who viewed the FDA proposed text at 30% of package perceived e-cigarettes as riskier than those who viewed the MarkTen text and the abstract text, but not those who viewed the smaller FDA text. As noted above, in a prior study on e-cigarettes, it was found that warning labels that mentioned e-cigarette ingredients did not increase risk perceptions; 31 however, in this study, the FDA proposed text at 30% of package, which mentions the product ingredient nicotine, generated higher ratings of risk perceptions among non-smoking women and smoking men.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Additionally, smoking men who viewed the FDA proposed text at 30% of package perceived e-cigarettes as riskier than those who viewed the MarkTen text and the abstract text, but not those who viewed the smaller FDA text. As noted above, in a prior study on e-cigarettes, it was found that warning labels that mentioned e-cigarette ingredients did not increase risk perceptions; 31 however, in this study, the FDA proposed text at 30% of package, which mentions the product ingredient nicotine, generated higher ratings of risk perceptions among non-smoking women and smoking men.…”
Section: Discussioncontrasting
confidence: 49%
“…30 In a study varying the warning statements on e-cigarette television advertisements, only those warning statements that focused on the negative aspects of the e-cigarette industry increased risk perceptions, whereas those that focused on the e-cigarette ingredients did not. 31 …”
Section: E-cigarette Labeling and Risk Perceptionsmentioning
confidence: 99%
“…348,403,712,720 Exposure to industry and ingredient warnings is associated with lower odds of intent to purchase ENDS. 714,734,747 Several studies have reported the presence of interior and exterior ENDS advertisements at tobacco retail outlets, 702,704,705,729 including one study which found that the ENDS advertisements featured flavored products at the eye level of children. 705 The total expenditure for ENDS advertisements across all media channels is increasing annually, 748,749 with a 52% increase from 2013 to 2014.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Nicotine is an addictive chemical” (FDA, 2016a). Beginning work suggests that e-cigarette health warnings can influence risk perceptions (Lee et al, 2017; Sanders-Jackson et al, 2015a). However, images of flavors on advertisements may interfere with health warning labels.…”
Section: Introductionmentioning
confidence: 99%